A Vision for Recovery Models of Ukrainian Cities - Idak, Yuliya (Journal of Public Governance, 2022)
Objectives: The direction of the research is determined by the necessity to generalise and systematise knowledge about the ways of forming and organising the material and spatial environment of human activity at the territorial level, adapted to the needs of modernity. It needs to meet the tasks of sustainable development. The result of the work will be the selection of basic models that will deepen the understanding of the nature of the modern functioning of the living environment as well as will be able to serve as an ideological basis for the reconstruction of war-ravaged settlements of Ukraine.Research Design & Methods: In order to explore the methods for the recovery of Ukrainian cities, I have studied the European experience of modern architectural and urban planning practice in the cities of Austria (Vienna, Graz, 2022), Germany (Munich, Bielefeld, 2022), and Poland (Kraków, Wrocław, 2022). The main part of the research begins with the selection of attributive categories and the generalisation of various ways of organising the residential environment, which are in the vision of modern European city planning and are expressed through specific concepts and categories. Next, it was about the models that fix the connections and relationships essential to the specified conditions.Findings: The formation of residential units in Austria, Germany, and Poland made it possible to identify five basic models. Each of them is guided by theories, principles, concepts, and categories relevant to the essence of the model, but they are united by the paradigm of sustainable development. The contents of the proposed models open as follows: the formal model is focused on the harmonisation of the urban environment; the classical model is about the compliance with industry standards; the socio-economic model is involves ensuring equal and sufficient opportunities for citizens; the ecological model values the preservation and restoration of the natural environment; and the conceptual model is about producing ideas based on innovations.Implications / Recommendations: Such models do not necessarily have to be tied to specific places, but they are capable of initiating the introduction of new ideas and technologies into the organisation of the material and spatial environment of human life.Contribution / Value Added: This work is largely related to the filling of a theoretical lacuna that exists in the theory of urban planning, and is provoked by the development of special forms of the social, material, and spatial organisation of the residential environment within a certain territory and under certain conditions.